ANALISIS PENGARUH KEPEMILIKAN MANAJERIAL, KEBIJAKAN UTANG, DAN PERTUMBUHAN PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2009, 2010, DAN 2011 - Gunawan, Stephani; Djohan, Widjaja (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2015)
This study aims to examine factors that affect company's dividend policy. Factors examined in this study are the managerial ownership, debt policy, and the company's growth. This study used a sample of 32 Indonesia Public  companies and who pay dividends during the years 2009 through 2011. The result showed that there is a significance and positive difference on the dividend policy of the company that owns and has no managerial ownership. It can be concluded that there are a negative effect of debt policy on dividend policy, while the company's growth variable has no significant effect on dividend policy.